Analisis Tax Buoyancy pada Asean-5 Tahun 2002-2016 - Setyoningrum, Dewi; Purwanti, Evi Yulia (Efficient: Indonesian Journal of Development Economics, 2020)
The fiscal deficit in developing countries is a major problem that has prompted government efforts to increase tax revenues. There is a positive relationship between tax and PDB. With tax buoyancy, the total response of tax revenue to changes in PDB can be measured by policy changes in the tax or administrative system. This study aims to identify analysis of tax buoyancy in ASEAN-5 countries (Indonesia, Philippines, Malaysia, Singapore, and Thailand) in 2002-2016. The analysis method in this study uses panel data regression analysis. Panel data regression analysis with the Commond Effect Model method is used to analyze the influence of the share of manufacturing sector, share of agricultural sector, share of import sector, share of service sector, budget deficit, corruption, and tax reform to tax buoyancy in ASEAN-5 countries (Indonesia, Philippines, Malaysia, Singapore, and Thailand in 2002-2016. The data used in this research is secondary data. The panel data regression results show that share of manufacturing sector, share of import sector, share of service sector, budget defici, corruption, and tax reform have a significant effect to tax buoyancy. The share of manufacturing sector with a coefficient of 1.30 as dominant factor affecting tax buoyancy. While for the share of agricultural sector has a coefficient -0.60 and insignificant effect on tax buoyancy in ASEAN-5 countries (Indonesia, Philippines, Malaysia, Singapore, and Thailand) in 2002-2016. Defisit fiskal di negara-negara berkembang adalah masalah besar yang mendorong upaya pemerintah untuk meningkatkan pendapatan pajak. Ada hubungan positif antara pajak dan PDB. Dengan apung pajak, total respons penerimaan pajak terhadap perubahan dalam PDB dapat diukur dengan perubahan kebijakan dalam sistem perpajakan atau administrasi. Penelitian ini bertujuan untuk mengidentifikasi analisis daya apung pajak di negara-negara ASEAN-5 (Indonesia, Filipina, Malaysia, Singapura, dan Thailand) pada tahun 2002-2016. Metode analisis dalam penelitian ini menggunakan analisis regresi data panel. Analisis regresi data panel dengan metode Commond Effect Model digunakan untuk menganalisis pengaruh pangsa sektor manufaktur, pangsa sektor pertanian, pangsa sektor impor, pangsa sektor jasa, defisit anggaran, korupsi, dan reformasi pajak terhadap kemampuan pajak di Negara-negara ASEAN-5 (Indonesia, Filipina, Malaysia, Singapura, dan Thailand pada tahun 2002-2016. Data yang digunakan dalam penelitian ini adalah data sekunder. Hasil regresi data panel menunjukkan bahwa pangsa sektor manufaktur, pangsa sektor impor, pangsa layanan sektor, defisiensi anggaran, korupsi, dan reformasi pajak memiliki pengaruh yang signifikan terhadap daya apung pajak. Pangsa sektor manufaktur dengan koefisien 1,30 sebagai faktor dominan yang mempengaruhi pajak apung. Sedangkan untuk pangsa sektor pertanian memiliki koefisien -0,60 dan pengaruh tidak signifikan tentang daya apung pajak di negara-negara ASEAN-5 (Indonesia, Filipina, Malaysia, Singapura, dan Thailand) pada tahun 2002-2016.